2014
DOI: 10.1370/afm.1601
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin and Levofloxacin Use and Increased Risk of Cardiac Arrhythmia and Death

Abstract: PURPOSE Azithromycin use has been associated with increased risk of death among patients at high baseline risk, but not for younger and middle-aged adults. The Food and Drug Administration issued a public warning on azithromycin, including a statement that the risks were similar for levofloxacin. We conducted a retrospective cohort study among US veterans to test the hypothesis that taking azithromycin or levofloxacin would increase the risk of cardiovascular death and cardiac arrhythmia compared with persons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
134
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(144 citation statements)
references
References 13 publications
6
134
1
3
Order By: Relevance
“…These studies vary in patient age, sex and comorbidity. Two studies reported no significant increase in the risk of ventricular arrhythmia associated with macrolide use relative to other antibiotics after 10 7 and 30 15 days of follow-up, although Rao and colleagues 7 reported an increased risk during the first 5 days of treatment only. The 7 remaining studies did not examine arrhythmia risk; however, 1 study did report a higher risk of cardiac events.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These studies vary in patient age, sex and comorbidity. Two studies reported no significant increase in the risk of ventricular arrhythmia associated with macrolide use relative to other antibiotics after 10 7 and 30 15 days of follow-up, although Rao and colleagues 7 reported an increased risk during the first 5 days of treatment only. The 7 remaining studies did not examine arrhythmia risk; however, 1 study did report a higher risk of cardiac events.…”
Section: Discussionmentioning
confidence: 96%
“…15,17,18 Similar to our results, 2 studies reported macrolide antibiotics to be associated with a lower risk of all-cause mortality than nonmacrolide antibiotics. 15,18 Rao and colleagues 7 reported an increased risk of allcause mortality during the first 5 days of treatment, but not for treatment days 6 to 10. We used the quality checklist developed by Downs and Black 55 to assess the reporting, external validity, internal validity and statistical power of the prior 9 studies (Appendix 12, available at www.cmaj.ca/lookup/ suppl/doi:10.1503/cmaj.150901 /-/DC1).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Leczenie kilkoma antybiotykami, takimi jak chinolony i azytromycyna, istotnie zwiększa ryzyko zgonu i zaburzeń rytmu serca [125,[745][746][747]. Wykazano, że inne antybiotyki z grupy makrolidów, w tym erytromycyna i klarytromycyna (które są również metabolizowane przez izoenzym 3A4 cytochromu P450), zwiększają ryzyko wielokształtnego VT i zgonu z przyczyn sercowych, zwłaszcza u kobiet [748].…”
Section: Interakcje Lek-lek (Z Powodu Stosowania Określonych Leków I unclassified
“…To better examine the link between macrolide treatment and plaque formation, the duration of follow-up should be at least several months because it often takes months to years for plaque formation to occur. However, for patients taking macrolides to treat common respiratory infections or soft-tissue infections, the duration of follow-up is usually no more than 1 month [28,29]. It is difficult to identify the cardiovascular death risk related to plaque rupture in such a short time.…”
mentioning
confidence: 99%